2011
DOI: 10.1038/nri2904
|View full text |Cite
|
Sign up to set email alerts
|

Presumed guilty: natural killer T cell defects and human disease

Abstract: Natural killer T (NKT) cells are important regulatory lymphocytes that have been shown in mouse studies, to have a crucial role in promoting immunity to tumours, bacteria and viruses, and in suppressing cell-mediated autoimmunity. Many clinical studies have indicated that NKT cell deficiencies and functional defects might also contribute to similar human diseases, although there is no real consensus about the nature of the NKT cell defects or whether NKT cells could be important for the diagnosis and/or treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
356
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(366 citation statements)
references
References 106 publications
6
356
1
3
Order By: Relevance
“…While the consequences of this impairment are unclear, several lines of evidence in other disease models suggest that dysfunction in NKT cells may mediate disease pathogenesis. 43 Interestingly, Dr. Nixon also found that HIV-1Viral Protein U (Vpu) directly affects CD1 antigen presentation, suggesting a role for NKT cells in host defense against HIV. 44 Immune exhaustion and central memory cells…”
Section: Immune Regulationmentioning
confidence: 99%
“…While the consequences of this impairment are unclear, several lines of evidence in other disease models suggest that dysfunction in NKT cells may mediate disease pathogenesis. 43 Interestingly, Dr. Nixon also found that HIV-1Viral Protein U (Vpu) directly affects CD1 antigen presentation, suggesting a role for NKT cells in host defense against HIV. 44 Immune exhaustion and central memory cells…”
Section: Immune Regulationmentioning
confidence: 99%
“…Therapeutic activation of iNKT cells in murine models can prevent tumor growth [182][183][184], ameliorate autoimmune [185,186] and metabolic [187] disease, and protect against microbial infection [188]. Numerical and functional iNKT cell deficiencies have been reported in a number of human diseases [189][190][191][192]. These findings led to clinical trials in humans for cancer involving the adoptive transfer of ex vivo expanded autologous DC, pulsed with a-GC, in the absence or presence of expanded iNKT cells [193][194][195].…”
mentioning
confidence: 99%
“…When stimulated, iNKT cells rapidly release a large amount of effector cytokines like IFN-γ and IL-4, both as a cell population and at the single-cell level. These cytokines then activate various immune effector cells, such as natural killer (NK) cells and dendritic cells (DCs) of the innate immune system, as well as CD4 helper and CD8 cytotoxic conventional αβ T cells of the adaptive immune system via activated DCs (3,4). Because of their unique activation mechanism, iNKT cells can attack multiple diseases independent of antigen and MHC restrictions, making them attractive universal therapeutic agents (3,4).…”
mentioning
confidence: 99%
“…These cytokines then activate various immune effector cells, such as natural killer (NK) cells and dendritic cells (DCs) of the innate immune system, as well as CD4 helper and CD8 cytotoxic conventional αβ T cells of the adaptive immune system via activated DCs (3,4). Because of their unique activation mechanism, iNKT cells can attack multiple diseases independent of antigen and MHC restrictions, making them attractive universal therapeutic agents (3,4). Notably, because of the capacity of effector NK cells and conventional αβ T cells to specifically recognize diseased tissue cells, iNKT cell-induced immune reactions result in limited off-target side effects (3,4).…”
mentioning
confidence: 99%
See 1 more Smart Citation